Bioconversion of Raw Glycerol From Waste Cooking-Oil-Based Biodiesel Production to 1,3-Propanediol and Lactate by a Microbial Consortium - Wang, Xiao-Li; Zhou, Jin-Jie; Sun, Ya-Qin; Xiu, Zhi-Long (Frontiers in Bioengineering and Biotechnology, 2019)
Waste cooking oil (WCO) is a sustainable alternative to raw vegetable oils and fats for biodiesel production considering both environmental and economic benefits. Raw glycerol from WCO-based biodiesel production (GWCO) is difficult to utilize via biological method, as multiple toxic impurities have inhibitory effects on microbial growth especially for pure cultures. In this work, four microbial consortia were selected from activated sludge by 30 serial transfers under different conditions. The obtained consortia exhibited lower diversity and species difference with the transfers. The consortium LS30 exhibited unique advantages for bioconversion of GWCO to 1,3-propanediol (1,3-PDO) and lactate (LA). Moreover, the fermentation could be performed economically under microaerobic and non-sterile conditions. The consortium consisted of 57.97% Enterobacter and 39.25% Escherichia could effectively convert 60 g/L GWCO to 1,3-PDO and LA in batch fermentation. In addition, this consortium exhibited better tolerance to fatty acid-derived crude glycerol (100 g/L), which demonstrated that specific toxic impurities in GWCO did pose a great challenge to microbial growth and metabolism. In fed batch fermentation, 27.77 g/L 1,3-PDO and 14.68 g/L LA were achieved. Compared with the consortium, a long lag phase in cell growth associated with a decreased glycerol consumption was observed in four single-strain fermentations. Furthermore, neither the consortium DL38 with excellent glycerol tolerance nor consortium C2-2M with high yield of 1,3-PDO could effectively transform GWCO into valuable products. The results demonstrated that the selected microbial consortium has the advanced adaptability to the toxic impurities in GWCO compared with other reported consortia and isolated single strain. This process can contribute to added-value use of GWCO.